Self-Efficacy Practice in Oral Presentation Through Self- Reflection among Pre-Service Teachers in Institute of Teacher Education - Tajuddin, Mimi Rita @ Aishah; Yaacob, Aizan; Rahman, Faizahani Ab. (South Asian Journal of Social Sciences and Humanities, 2021)
Self-efficacy is the driving force that makes people pursue a goal and overcome obstacles. Through numerous studies, students with a high sense of efficacy have the capacity to accept more challenging tasks, have higher abilities to organize their time, increase persistence in the face of obstacles, and exhibit lower anxiety levels. In this study, pre-service teachers have oral presentation anxiety, which overcomes their feelings by practicing self-efficacy such as intentionality, forethought, self-reactiveness, self-reflectiveness and self-enhancement through self-reflections after oral presentations. Data for this study were obtained through self-reflection and interviews administered to 13 pre-service teachers at an Institute of Teacher Education to investigate their self-efficacy practices to overcome oral performance anxiety in presenting the topics and analyzed thematically. Self-reflection is obtained through Schoology Learning Management System (LMS), written self-reflection and interviews. The pre-service teachers practiced self-efficacy that is self-enhancement – therefore, this information contributes to the new knowledge following earlier research. The findings revealed that pre-service teachers' self-reflection depicted their self-efficacy practice such as intentionality, forethought, self-reactiveness, self-reflectiveness and self-enhancement. The study's practical implications show that self-reflection has a positive impact on the pre-service teachers' oral presentation skills. This significantly contributes to turning the pre-service teachers into independent, life-long learners.
Keywords: Self-efficacy; pre-service teachers; self-reflection; second language learning; oral performance anxiety